Screening of Anemia in Patients with Coronary Heart Disease in Outpatient Practice Using a Computer Monitoring System - Alexey Y. Simion; Andrey V. Budnevsky; Evgeniy S. Ovsyannikov; Natalia E. Nekhaenko; Nadezhda I. Ostroushko; Natalia V. Malyukova (International Journal of Biomedicine, 2022)
The aim of this study was to assess the prevalence, structure, and influence of anemic syndrome on the main health indicators of patients with coronary heart disease (CHD), including the main QOL parameters. Methods and Results: The study included 1210 patients (309 men and 901 women) with an average age of 67.57±9.35 years who were registered at the dispensary with CHD (angina pectoris CCSA classes II-IV) in 2 Regional Hospitals. With the help of the computer program “Monitoring system for patients with anemia syndrome,” medical records from 2 randomly selected primary care areas were analyzed. The data directly related to anemia, comorbid pathology, and previous treatment formed the main part of the statistical data. The QOL was evaluated using the 36-Item Short Form Survey (SF-36) questionnaire. The FACT-An questionnaire was used to account for the characteristic symptoms, and their severity, accompanying anemia. Our findings indicate the presence of anemia in 500(41.3%) patients (355/71% women and 145/29% men). The average age of the patients with diagnosed anemia was 65.34±6.37 years in men and 63.49±7.05 years in women. Anemia of mild severity was observed in 410(82%) patients, moderate severity in 75(15%) patients, and severe anemia in 15(3%) patients. IDA was detected in 467(93.4%) cases and B12-deficiency anemia in 33(6.6%) cases. We found a negative correlation between the blood iron level and age (r=-0.56, P<0.05), which can indirectly indicate the progression of latent iron deficiency with age in CHD patients. All 500 CHD patients with anemia were included in Group 1. Group 2 included 710 CHD patients without anemia. In Groups 1 and 2, angina severity according to CCSA classification was as follows: CCSA class II - 186(37.2%) and 456(64.2%) cases (P=0.000), CCSA class III – 248(49.6%) and 196(27.6%) cases (P=0.000), and CCSA class IV - 66(13.2%) and 58(8.2%) cases (P=0.005), respectively. Group 1 patients, in contrast to Group 2 patients, had the following characteristic clinical features: palpitation (48.2% vs. 35.0%, P=0.000), higher HR (81±9.5 bpm vs. 71.8±8.7 bpm, P=0.000) and respiratory rate (18.9±1.1 vs 18.3±1.2 per minute, P=0.000). The assessment of the impact of anemia on QOL by FACT-An revealed a statistically lower score in Group 1 than in Group 2 (32.0±5.7 vs. 44.0±6.5, P=0.000). We found a positive correlation between the Hb level and the average FACT-An score (r=0.54, P<0.05) Patients in Group 1 demonstrated a low level of QOL in the physical and mental domains, according to SF-36, in comparison with Group 2. Correlation analysis revealed a direct relationship between the Hb level and the average score of the PF (physical functioning) scale (r=0.52, P<0.05)) and PCS (physical component summary) (r=0.38, P<0.05)) of the SF-36 questionnaire. The observed high incidence of anemic syndrome in CHD patients with angina pectoris (CCSA class II-IV) requires special attention due to the high impact on the QOL of patients and aggravation of the course of the underlying disease.